Improved Sensitivity RF Photonics Doppler Frequency Measurement System - Hossein Emami; Mohammadreza Hajihashemi; Sayed Ehsan Alavi (IEEE Photonics Journal, 2016)
An improved sensitivity Doppler frequency measurement system based on microwave photonics technology was demonstrated practically. The system employs a four-wave mixing effect to achieve broad radio-frequency (RF) frequency measurement. In addition, a lock-in amplification technique was utilized to achieve high-measurement sensitivity. The system is, thus, capable of Doppler frequency estimation of radar echoes with a carrier frequency up to 40 GHz and a power level as low as $-$ 35 dBm.